Discovery of a novel Parvovirinae virus, porcine parvovirus 7, by metagenomic sequencing of porcine rectal swabs - Palinski, Rachel M.; Mitra, Namita; Hause, Ben M. (Virus genes, 2016)
Parvoviruses are a diverse group of viruses containing some of the smallest known species that are capable of infecting a wide range of animals. Metagenomic sequencing of pooled rectal swabs from adult pigs identified a 4103-bp contig consisting of two major open reading frames encoding proteins of 672 and 469 amino acids (aa) in length. BLASTP analysis of the 672-aa protein found 42.4 % identity to fruit bat ( Eidolon helvum ) parvovirus 2 (EhPV2) and 37.9 % to turkey parvovirus (TuPV) TP1-2012/HUN NS1 proteins. The 469-aa protein had no significant similarity to known proteins. Genetic and phylogenetic analyses suggest that PPV7, EhPV2, and TuPV represent a novel genus in the family Parvoviridae . Quantitative PCR screening of 182 porcine diagnostic samples found a total of 16 positives (8.6 %). Together, these data suggest that PPV7 is a highly divergent novel parvovirus prevalent within the US swine.